2018
DOI: 10.3390/molecules23071788
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Anthocyanin from Myrica rubra against Cerebral Ischemia-Reperfusion Injury via Modulation of the TLR4/NF-κB and NLRP3 Pathways

Abstract: Myrica rubra (MR) is rich in anthocyanins, and it has good anti-cancer, anti-aging, antioxidant, and antiviral effects. The proportion of disability and death caused by ischemic stroke gradually increased, becoming a major disease that is harmful to human health. However, research on effects of anthocyanin from MR on cerebral ischemia-reperfusion (I/R) injury is rare. In this study, we prepared eight purified anthocyanin extracts (PAEs) from different types of MR, and examined the amounts of total anthocyanin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 37 publications
0
56
0
Order By: Relevance
“…The compounds (1,3,4,7,8,9,11,12,19,21,23, and 27) were dissolved in dimethyl sulfoxide (DMSO) and, respectively, diluted to the required concentration (0.02, 0.2, 2, 20 mg mL À1 ) using a culture solution. During the logarithmic phase of adherence of HUVECs, pancreatin was added.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The compounds (1,3,4,7,8,9,11,12,19,21,23, and 27) were dissolved in dimethyl sulfoxide (DMSO) and, respectively, diluted to the required concentration (0.02, 0.2, 2, 20 mg mL À1 ) using a culture solution. During the logarithmic phase of adherence of HUVECs, pancreatin was added.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…Aer dissociation, the culture solution was added (10% DMEM of fetal bovine serum), and this cell suspension was 105 units per mL. Suspension (100 mL) was added into each well of a 96-well culture plate and cultured for 24 h. The HUVECs were divided into 13 groups and each group was treated with L-NAME (100 mmol L À1 ), L-NAME and compounds (1,3,4,7,8,9,11,12,19,21,23,27) for 24 h aer the culture solution was removed, and with the control group only using culture solution. The supernatant was discarded and 10 mL of fresh MTT solution (5 mg mL À1 ) was added into each well.…”
Section: Cell Proliferation Assaymentioning
confidence: 99%
“…during reperfusion) with lower doses of purified C3G (2 mg/kg i.p administered or 10 mg/kg FIGURE 3 | In cerebral ischemia, anthocyanins (ACNs) reduce neuroinflammation by: (i) decreasing the expression of Toll-like receptor 4 (TLR4), an activator of nuclear factor kappa B (NF-kB), and tumor necrosis factor-a (TNF-a) proinflammatory cytokine expression (Cui et al, 2018). (ii) Reducing the expression of inducible nitric oxide synthase (iNOS) and neuronal nitric oxide synthase (nNOS), targets of NF-kB, and as a consequence NO content at cerebral level, thus reflecting a reduction in brain damage (Di Giacomo et al, 2012;Cui et al, 2018). A significant increase of eNOS was observed which may result in vasorelaxation with a consequent attenuation of the ischemic insult and promotion of functional recovery of the ischemic zone (Di Giacomo et al, 2012).…”
Section: Cerebral Ischemiamentioning
confidence: 99%
“…Safaeian et al demonstrated that C3G extracted from Echium amoenum petals was efficient in reducing myeloperoxidase activity, an indicator of leukocyte infiltration, in the brain tissue following cerebral ischemia induced by bilateral common carotid arteries occlusion/reperfusion in rats [ 169 ]. In a similar study involving a middle cerebral artery occlusion/reperfusion as an animal model of ischemia, anthocyanins isolated from Myrica rubra , mainly C3G (roughly 95%), were given to mice for seven days prior to surgery [ 118 ]. The authors showed that this anthocyanin extract were able to decrease the protein expression levels of TLR4, TNF-α, NLR family pyrin domain-containing protein 3 (NLRP3) and IL-18 in cerebral cortex, preventing the inflammatory response associated with these signaling pathways and suggesting that TLR4 might be an additional target for anthocyanins [ 118 ].…”
Section: Anti-neuroinflammatory Activity Of Anthocyanins and Theirmentioning
confidence: 99%
“…In a similar study involving a middle cerebral artery occlusion/reperfusion as an animal model of ischemia, anthocyanins isolated from Myrica rubra , mainly C3G (roughly 95%), were given to mice for seven days prior to surgery [ 118 ]. The authors showed that this anthocyanin extract were able to decrease the protein expression levels of TLR4, TNF-α, NLR family pyrin domain-containing protein 3 (NLRP3) and IL-18 in cerebral cortex, preventing the inflammatory response associated with these signaling pathways and suggesting that TLR4 might be an additional target for anthocyanins [ 118 ]. Also, the potential neuroprotective role of vanillic acid against pathological alterations in adult rats subjected to two-vessel occlusion and subsequent reperfusion has been reported.…”
Section: Anti-neuroinflammatory Activity Of Anthocyanins and Theirmentioning
confidence: 99%